Cutaneous pseudolymphoma: An enigma - B M Shashikumar; M R Harish; Kirti P Katwe; M Kavya (Wolters Kluwer Medknow Publications, 2017)
Cutaneous pseudolymphoma, also called lymphoid infiltrates of the skin mimicking lymphomas, is defined as reactive polyclonal benign lymphoproliferative process predominantly composed of either B-cells or T-cells, localized or disseminated. A 62-year-old male presented with multiple asymptomatic swellings over the posterior aspect of the left ear of 1-year duration. On examination, multiple nodules were present over the left retroauricular area, 2 of which were skin colored, firm, and nontender. Histopathology revealed pseudolymphoma with the features of a dense diffuse and nodular infiltrate of small and large lymphocytes and histiocytoid cells involving the whole of reticular dermis and extending to subcutis. A patch test was done using Indian standard battery series showed positive reaction - 2+ for paraphenylenediamine. A diagnosis of cutaneous pseudolymphoma was made. The lesions were treated with intralesional Triamcinolone acetonide injection 10 mg/ml for 2 sittings, 3 weeks apart following which there was remission of the nodules. Pseudolymphomas are benign but persistent lymphoid proliferations in the dermis, which may be difficult to distinguish from a low-grade malignant lymphoma. Pseudolymphomas are classified according to the histological components into B-cell and T-cell variants. So far no case of cutaneous pseudolymphoma suggestive of insect bite with coincidental paraphenylenediamine allergy has been reported. Hence, this case is reported as its histopathology was suggestive of pseudolymphoma secondary to insect bite reaction.